OTRI: Agenda de investigación - F. Vendrell Herrero; Pedro Ortín Ángel (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
The present paper presents different lines of work in order to extend the current empirical research about the role of the technology transfer offices (TTO). Those lines of research come from the new advances in the micro economic analysis of TTOs and focus on questions such as the economic reasons for the existence of TTOs, the incentives scheme of the scientist and the best way of transferring technology, licensing or spinning-off. Most of these lines still remain without analyzing and the existent evidence comes basically from US and UK. The empirical research should foment new advances in the theoretical approach.
Keywords: 330; TTO; spin-off; licensing; design of contracts; university